Ælfric's De temporibus anni - Aelfric, Abbot of Eynsham (Anglo-Saxon texts, 2009)
De temporibus anni, a concise handbook of calendar and computus, astronomy and natural science, dates from the late tenth century. It seems to have circulated anonymously, but analysis of its language and content shows it to be by Ælfric, one of the most prolific and widely-studied authors of Anglo-Saxon England. Unlike the earlier works of Bede and Isidore, it is written in the vernacular (despite its Latin title), possibly the earliest such work in a vernacular language in western Europe. This new edition incorporates the fruits of modern research into the scientific and religious background to the work, as well as the findings of recent studies on palaeography and textual criticism. It is also the most comprehensive edition yet produced, including notes, glossary and bibliography, and the first modern English translation (presented en face) for some 140 years. By means of these, and the inclusion of a detailed introduction and commentary, it renders the work more accessible both to those interested in the history of science and to students of Anglo-Saxon language and literature. Dr MARTIN BLAKE works with medieval manuscripts in the Department of Manuscripts and University Archives at Cambridge University Library.